Refugee Education under International NGOs: A Major Shift from National Institutions to Patron–Client Relations - Sheraz Akhtar; Elizabeth Rata (Social Sciences, 2022)
What happens when a group of structurally powerless refugees exist within a nation-state’s territory but outside its regulatory institutions? An empirical study of the education of Pakistani Christian refugees in Bangkok, Thailand, identifies an entrenched gap between the education provided by INGOs and Pakistani Christian refugee expectations of the academic education of their children. We generalise from the specific problem of the entrenched educational discrepancy to a deeper structural inequality by using a ‘realist conceptual methodology’ characterised by the type of co-dependency found in the historical form of patron–client relations. The patron–client relationship is the outcome of being placed outside a nation-state’s institutions and the co-dependence that the relationship itself creates between the INGO providers and the refugees. We suggest that patron–client theory is a useful conceptual tool with which to explain the sociopolitical position of groups today who find themselves placed outside a modern nation-state’s institutions.